Od rozmowy do korpusu Czyli jak zbierać i archiwizować dane mówione - Zaśko-Zielińska, Monika; Majewska-Tworek, Anna; Śleziak, Marta; Tworek, Artur (Quaestio, 2020)
The book From the Conversation to the Corpus, or How to Collect and Archive Spoken Language Data examines research on the spoken variant of Polish. The authors draw attention to the value of spoken language data and the role it plays in general dictionaries and in Polish language corpora, taking into account traditional publications as well as modern search engines and Internet databases. The authors present multi-faceted Laboratory and the Phonetics Laboratory at the University of Wrocław. The publication describes at length two projects that have been developed in cooperation with the CLARIN-PL consortium: the recovery and archiving of spoken language data obtained as part of re search on the variants of spoken Polish used in cities (with the data that was collected in the 1990s), as well as the implementation of the first stage of the large project “Language Biographies of Lower Silesia – the oldest generation,” whose aim was to record and transcribe biographical interviews with the oldest inhabitants of Lower Silesia and the Opole region. A measurable effect of both projects has been the development of documentation that can be used in similar types of research. In the book’s appendix, the reader may find templates of useful documentation, which include a letter to the data provider, a conversation script, a metadata card, a description of the interview setting card, a text to be read by the data provider, and a thank-you note. The authors also adapted the Dublin Core metadata schema, adjusting it to the needs of data acquisition procedures that apply the method of the biographical interview.
Keywords: speech; spoken Polish; transcription; annotation; gerontolinguistic; biografical interview; metadata; research ethics; archiving